2017
DOI: 10.1093/eurpub/ckx057
|View full text |Cite
|
Sign up to set email alerts
|

International migrants’ use of emergency departments in Europe compared with non-migrants’ use: a systematic review

Abstract: The principal finding of this review is that migrants utilize the ED more, and differently, to the native populations in EEA countries. The higher use of the ED for low-acuity presentations and the use of the ED during unsocial hours suggest that barriers to primary healthcare may be driving the higher use of these emergency services although further research is needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
70
0
8

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 79 publications
(88 citation statements)
references
References 35 publications
10
70
0
8
Order By: Relevance
“…Also consistent with the present findings, two studies that accounted for system criteria found higher rates of non-urgent use among migrants, 12,18 and another that considered only patient criteria reported lower rates of non-urgent use by migrants. 15 In a systematic review, a higher rate of gynecologic consultations and more ED use for low-acuity presentations was found among migrants than among non-migrants in Europe, 12 The reference group was non-migrants. b P<0.05.…”
Section: Acculturation Of Migrantssupporting
confidence: 91%
See 4 more Smart Citations
“…Also consistent with the present findings, two studies that accounted for system criteria found higher rates of non-urgent use among migrants, 12,18 and another that considered only patient criteria reported lower rates of non-urgent use by migrants. 15 In a systematic review, a higher rate of gynecologic consultations and more ED use for low-acuity presentations was found among migrants than among non-migrants in Europe, 12 The reference group was non-migrants. b P<0.05.…”
Section: Acculturation Of Migrantssupporting
confidence: 91%
“…Researchers have used varying definitions of urgency and non‐urgency, which makes an appraisal of the present findings difficult. Nonetheless, studies with a similar approach have reported comparable results . For example, our research group previously developed an inappropriateness index for ED or GED utilization that combined both patient and system perspectives, reporting that ethnicity was not a significant predictor for inappropriate use of EDs, analogous to the current findings based on a composite index.…”
Section: Discussionsupporting
confidence: 69%
See 3 more Smart Citations